Supercritical Carbon dioxide and flaxseed oil like functional food - Regnicoli, G.F.; Marconi, O.; Perretti, G. (Progress in Nutrition, 2012)
Literature shows the functional food properties of Flaxseeds (Linum usitatissimum L.). Flaxseeds are rich in Alpha-Linolenic Acid (ALA) and are interesting for their dietary fiber and proteins content and for the presence of helpful minor compounds, important for human consumption, like lignans, phytoestrogens that can have hormone-like effects in humans. In fact, diets introducing flaxseed oil show also useful effects on diseases like lowering blood pressure, particularly in middle age dyslipidaemia and reducing the risk of myocardial infarction. Organic solvents are generally used to obtain a high extraction yield of flaxseed oil. An alternative method is expression (mechanical extraction) that offers a remarkable reduction of environmental impact, but with lower extraction yield in comparison with solvents. Another method of extraction could be the use of supercritical fluids. The same authors already studied the Supercritical Carbon dioxide (SC-CO2) as potential solvent for flaxseed oil extraction. In this study a comparison of the technological and qualitative effects on the flaxseed oils obtained by neat SC-CO2 extraction and by SC-CO2 added with ethanol as co-solvent extraction was conducted. The extraction capacity of important polar compounds like polyphenols was determined, too. The results of this study confirm the ability of SC-CO2 in obtaining a high quality product like flaxseed oil.Anidride carbonica supercritica e olio di lino come alimento funzionaleLa letteratura mostra le proprietà funzionali dell’olio di lino alimentare (Linum usitatissimum L.). I semi di lino sono ricchi in Acido Alfa-Linolenico (ALA), e sono interessanti per il loro contenuto in fibra e in proteine e per la presenza di preziosi composti minori, importanti per il consumo umano. Infatti, le diete comprendenti olio di semi di lino dimostrano effetti utili contro disordini come quelli legati alla bassa pressione sanguigna, particolarmente per la dislipidemia e nella riduzione del rischio di infarto del miocardio. Normalmente, per l’ottenimento di olio di semi di lino vengono utilizzati solventi organici, i quali permettono alte rese. Un’alternativa è posta dalla spremitura (estrazione meccanica), che preserva maggiormente il prodotto e l’ambiente, ma con rese inferiori rispetto ai solventi. Un altro metodo potrebbe essere l’utilizzo di Fluidi Supercritici. Gli stessi autori hanno studiato precedentemente l’impiego di CO2 supercritica (SC-CO2) come potenziale solvente per l’estrazione di oli di semi di lino. In questo studio sono stati realizzati dei confronti degli effetti tecnologici e qualitativi su oli di semi di lino estratti mediante l’impiego di SC-CO2 pura e SC-CO2 addizionata di etanolo come co-solvente. È stata determinata anche la possibilità di estrazione di importanti composti polari quali i polifenoli. I risultati di questo studio confermano la capacità estrattiva della SC-CO2 nell’ottenimento di un prodotto alimentare di elevata qualità quale l’olio di lino.